Robotic Device for Cleaning and Monitoring Photovoltaic Panel Arrays - Muhammad Arif Hazmi Bin Abd Aziz (Progress in Engineering Application and Technology, 2021)
Technology has improved from time to time including in getting a better performance of a photovoltaics (PV) panels yet less worked needed to maintain the output. However, solar array is usually being placed in an open area, its surfaces are likely to be exposed to impurities that can reduce the solar power generation. Hence, this paper proposed an efficient way to cleaning a PV array as well as controlling and monitoring the panels via IoT in order to improve the voltage and current output. In the proposed prototype, the output that need to be considered are PV panels surface image, voltage and current output from the PV panels and the efficiency of the robot cleaning to clean more than one panel. The results show that the distance-monitoring model analyses the sensing data and the specific method for measuring the values of adapted sensors and also the self-controlling of the output linked equipment. Since solar has been a high demand market currently, this prototype should be able to operate and fulfill all the market demand.